When muscle quivers and undulates. Issue 7 (22nd July 2022) - Rebello, Alex; Asif, Mohd; Dhanusha, Kumbha; Haritha, Bandi; Narmada, Nangadda; Poudel, Ram Chandra
Abstract: We describe a patient who presented with fatigue and pulling sensation in his lower limbs. He had continuous muscle contractions over his trunk (myokymia) which pointed towards the diagnosis of Isaacs syndrome which was confirmed by strongly positive CASPR2 antibodies in blood. Abstract : Isaacs syndrome is a neuromuscular disorder with progressive stiffness and continuous contractions in muscles. The cause is usually uncertain; however, many are autoimmune mediated. The diagnosis may be made clinically by a proper examination, which can reveal myokymia. The presence of antibodies against voltage‐gated potassium channels confirms the diagnosis.